F<span> + </span>g)(x<span>) = </span>f(x<span>) + </span>g(x); (f<span> - </span>g)(x<span>) = </span>f(x<span>) - </span>g(x): (f<span> · </span>g)(x<span>) = </span>f(x<span>) · </span>g(x<span>) ..., let </span>f(x) = 5x+2<span> and </span>g(x<span>) = </span><span>x2</span>-1. <span>4. </span>f(4)=5(4)+2<span>=22 and </span>g(4)=42-1=15 ... (fog)(x<span>) = </span>f<span> [ </span>g(x<span>) ] = </span>f<span> [ 4x2 ] = sqrt( </span><span>4.2</span><span> ) = </span>2<span> | </span>x<span> |; (</span>gof)(x<span>) = </span>g<span> [</span>f(x<span>) ] = </span>g [ s
Answer:
(x-2) (x^2 -5)
Step-by-step explanation:
x^3 − 2x^2 − 5x + 10
We will factor by grouping
Take and x^2 out of the first two terms and -5 out of the last two terms
x^2 (x-2) -5(x-2)
Now we can factor out (x-2)
(x-2) (x^2 -5)
Answer:
the triangles are not similar.
Step-by-step explanation:
(64y100)1/2
1/2×64y 1/2×100
32y50